Community-based conservation strategies for wild edible plants in Turkana County, Kenya - Oduor, Francis; Kaindi, Dasel Mulwa; Abong, George; Thuita, Faith; Termote, Céline (MDPI, 2025)
In arid Turkana County, over 90% of the population is food insecure, and wild edible plants (WEPs) provide 12–30% of dietary intake. However, climate change and overexploitation threaten these crucial resources. This study employed sequential qualitative methods to investigate community perceptions, conservation priorities for WEPs, barriers, and necessary actions in Turkana. It combined participatory community workshops and expert validation interviews. The research revealed critical threats to WEP availability, including climate change, shifting cultural practices, and a lack of natural regeneration. Key conservation barriers included intergenerational knowledge gaps, inadequate policy implementation, and conflicts between immediate needs and long-term conservation goals. In developing conservation plans, the stakeholders identified and prioritized WEP species based on food value, medicinal properties, cultural significance, utility, and drought resistance. The co-developed conservation strategy emphasized both in situ protection measures, such as community awareness programs and local policy enforcement mechanisms, and restoration actions that include planting prioritized WEPs in home gardens and community spaces. Collaborative roles for communities, non-governmental organizations, researchers, and government actors were identified to provide training, resources, and technical support. This strategy also emphasizes the need for incentivization through food/cash-for-work programs and small business grants to promote alternative livelihoods. The strategies align with some of the most-utilized conservation frameworks and principles, and present new ideas such as integrating indigenous knowledge. Expert validation confirmed the feasibility of proposed actions, highlighting the importance of multi-stakeholder approaches. This study contributes to expanding our knowledge base on community-based conservation and provides insights for policymakers, emphasizing WEPs’ critical role in food security, cultural preservation, and ecological resilience. The findings could serve as a model for similar initiatives in other arid regions facing comparable challenges.